2018
DOI: 10.1111/acel.12730
|View full text |Cite
|
Sign up to set email alerts
|

Mice with reduced expression of the telomere‐associated protein Ft1 develop p53‐sensitive progeroid traits

Abstract: SummaryHuman AKTIP and mouse Ft1 are orthologous ubiquitin E2 variant proteins involved in telomere maintenance and DNA replication. AKTIP also interacts with A‐ and B‐type lamins. These features suggest that Ft1 may be implicated in aging regulatory pathways. Here, we show that cells derived from hypomorph Ft1 mutant (Ft1 kof/kof) mice exhibit telomeric defects and that Ft1 kof/kof animals develop progeroid traits, including impaired growth, skeletal and skin defects, abnormal heart tissue, and sterility. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 43 publications
(63 reference statements)
1
39
1
Order By: Relevance
“…We described that AKTIP dysfunction causes DNA replication and telomere defects, which in turn generate DNA damage activation and cell senescence [63]. Consistently with the connection of AKTIP both with lamins and DNA function, hypomorphic mice (Ft1 kof/kof , Ft1 Knock out first) displayed premature aging defects, including reduced body size, lipodistrophy, altered bone density and kyphosis [64]. We demonstrated that the phenotype is partly rescued by co-depletion of p53, pointing to the interplay between DNA damage and progeria.…”
Section: Dna Replication Is Altered In Progeroid Syndromesmentioning
confidence: 66%
See 1 more Smart Citation
“…We described that AKTIP dysfunction causes DNA replication and telomere defects, which in turn generate DNA damage activation and cell senescence [63]. Consistently with the connection of AKTIP both with lamins and DNA function, hypomorphic mice (Ft1 kof/kof , Ft1 Knock out first) displayed premature aging defects, including reduced body size, lipodistrophy, altered bone density and kyphosis [64]. We demonstrated that the phenotype is partly rescued by co-depletion of p53, pointing to the interplay between DNA damage and progeria.…”
Section: Dna Replication Is Altered In Progeroid Syndromesmentioning
confidence: 66%
“…We observed progeroid traits in a mouse model defective in a gene implicated in DNA function named AKTIP (in humans and Ft1 in mouse) [63][64][65]. We described that AKTIP dysfunction causes DNA replication and telomere defects, which in turn generate DNA damage activation and cell senescence [63].…”
Section: Dna Replication Is Altered In Progeroid Syndromesmentioning
confidence: 99%
“…A reduction in AKTIP expression resulted in multiple telomeric signals coupled with the activation of DNA damage markers and with the disorganization of chromatin. In mice, Ft1 reduction causes premature aging defects that are partially rescued by reducing the expression of the DNA damage sensor p53 (15, 16). AKTIP is distributed in the nucleus in a punctate pattern and decorates the nuclear rim in interphase (12, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanistic path to disease is complex in humans due to ethical issues, unavailability of controls and high costs of human research. As a result, studies mostly rely on the use of models, including human 3D cultures and stem cell based systems (Riminucci et al, 2006 ; Simão et al, 2015 ), or, for organismal analyses, genetically engineered mice (Baraban, 2007 ; Saggio et al, 2014 ; Remoli et al, 2015 ; La Torre et al, 2018 ). One of the way in which epilepsy has been modeled in mice is via the inactivation of genes implicated in ion channels (Yu et al, 2006 ; Baraban, 2007 ; Glasscock et al, 2012 ), or of genes encoding for neurotransmitter receptors (Fonck et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…AKTIP/Ft1 reduction causes telomere aberrations, DNA instability and cell senescence (Burla et al, 2015 ). In vivo , the genetic reduction of Ft1 causes premature aging defects including skeletal alterations and lipodystrophy (La Torre et al, 2018 ). AKTIP/Ft1 interacts with lamins (Burla et al, 2016a , b ), pivotal elements for the control of nuclear architecture and DNA function, including DNA repair, replication and transcription (Dittmer and Misteli, 2011 ).…”
Section: Introductionmentioning
confidence: 99%